Case Study in the Power of Collaboration: Planning Process for the Kansas Educational Leadership Institute - Mary Devin; Debbie Mercer; Mike Mathes; Tom Trigg; Sharon Zoellner (Educational Considerations, 2013)
Systematic statewide support for the recruitment, development, and retention of quality leaders in schools and school districts was not a new idea in Kansas in late 2010, but at best it was at an elusive concept. Diverse groups had considered it among components of a long-range commitment to move Kansas education quality from good to great, but no plan for creating such a system was in place.
Keywords: collaboration; No Child Left Behind; Kansas Education; diverse; stakeholder. higher education; initiative; administrators; Professional learning; leadership